Cytotoxicity Assay, Antioxidant Activity and Investigation of Bioactive Compounds Using GC-MS in the Leaves Extracts of Cinnamomum tamala (Buch. -Ham.) - Semwal, Sushmita; Kumar, Neeraj; Joshi, Bhuwan Chandra; Budhlakoti, Pankaj (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Cinnamomum tamala (Lauraceae), commonly known as Tejpaat or Bay leaves, find application in foods, along with traditional uses for curing a number of ailments. The objective of the current study was to investigate the cytotoxic efficacies of different solvent extracts of Cinnamomum tamala (Buch. -Ham.) leaves on some cancer cell lines. Materials and Methods: The powdered leaves were extracted using petroleum ether, chloroform, ethyl acetate and ethanol and tested for the presence of phytoconstituents. The extracts were evaluated for cytotoxic activity using four cell lines i.e. MDA-MB-231, A549, HepG2 and HT-29 by MTT assay. The most effective extract was then evaluated for antioxidant activity using the DPPH assay. The extract exhibiting notable cytotoxic activity was further subjected to GC-MS profiling to determine its bioactive constituents. The cytotoxicity shown by all the extracts was time and dose-dependent at low concentrations. Results: The Cytotoxic activity shown by Chloroform Extract (CTCE) was effective against human colon cancer cell line (HT-29) having IC50 26.15 μg/mL. CTCE also revealed good DPPH antioxidant activity with IC50 46.31±0.15 μg/mL. The GC-MS profiling of CTCE showed 50 constituents, among which the component phytosterols like γ-Sitosterol and Campesterol were present. Conclusion: This study highlights the greater cytotoxicity of CTCE observed on HT-29 cell lines. The cytotoxicity can be due to presence of detected compounds, particularly phytosterols in the CTCE. So, it can be concluded that Cinnamomum tamala leaves have significant cytotoxic activity and suggest further isolation of active components and evaluating their mechanism(s) of action
Keywords: Antioxidant; Cancer cell lines; Cinnamomum tamala; Cytotoxic Activity